UPAYA HUKUM DAN PENYELESAIAN WANPRESTASI OVERMACHT DALAM PERJANJIAN PADA PERUSAHAAN PEMBIAYAAN NON BANK - Indah Trie Risky (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT Fill an operating lease agreement with regard Directorate General Announcement of Monetary No. PENG-307/DJM/III.1/7/1974 Guidelines on the Implementation of the Leasing Regulation is : Provisions concerning the object of the agreement, The contract period, The rental price, And the manner of payment, The rights and obligations of the parties, Delivery (Delivery date and delivery limits), The expiration of the agreement.Constraints faced in the leasing contract among others regulations on leasing regulations in indonesia is still relatively overlooked that indonesia still has not set the statud specifically includes about leasing, constraints are technic that the lessor requires expertise appropriate ields and master each problem specifically related to the lease agreement. After the lessor having problems listed above, then the lessee itself usually also obtain constraints in the form of pressure that must be the availability of funds to make the supply of capital goods to the lessor. So inevitably, lesse parties have agreed to the deal they made and the provisions that have been included even though lessee by the lessor reluctant to agree to such provisions, because in this case the lessor shall be fully responsible for all risks and constraints in the lease agreement.Efforts law and settlement of default and coercion among other : in case of default in the form of late payment of rent, then the lessor is entitled to make the penalties for late payment of the amount specified in the agreement. Howeve in pratice, he lessor will provide warning both verbally (by telephone) or by mail to the lessee. The lessor also still provides a grace period to the lessee to settel arrears of rent to the lessor as well as in the event of late payment made less than three days from the due date, then the lessee is not subject to penalties ; in case of default in the form of mortgage capital goods and capital goods pemindahtangganan lease rights to third parties, then the lessor immediately take the following acions : the day after it emerged that the pledged collateral, lessor informanya immediately sent a team to pull the capital goods based on a power of attorney made by the parties in conjunction with the approval of the lease agreement between the brand ; in the case of a lessee who is accused of negligent and requested that sanctions be given to him on the negligence, can defend themselves by filing a reason to break free of the sanctions. The reason the lessee to free themselves from the sanctions for negligence, on is by suing any state force (coercion)